Night Market Role Play to Introduce Financial Literacy to 4-5 Year Old Children at PGRI 5 Kindergarten, Kalipare, Malang Regency - Rizky Dera Maulidyah; Rina Wijayanti; Henny Anggraini (Journal of Creative Power and Ambition (JCPA), 2026)
This research was conducted at TK PGRI 5 Kalipare with 13 children aged 4-5 years, most of whom had not yet understood the basic concepts of financial literacy, such as how to earn, manage, and use money wisely. The children tend to view money solely as a means to buy snacks without understanding its value and function. Previous teaching approaches using simple buying and selling games failed to provide deep understanding, so a more engaging and meaningful method such as role-playing was needed. The purpose of this study was to introduce financial literacy through a night market role-playing activity for children aged 4-5 years at TK PGRI 5 Kalipare, Malang Regency. This research used a Classroom Action Research (CAR) method based on Gerald Susman's model. The study was conducted in two cycles, with two meetings in each cycle, between July 7-14, 2025. The research subjects were 13 students from Group A at TK PGRI 5 Kalipare. Data collection instruments included observation sheets and interview guides. The results showed that the pre-cycle average was 33.3%. In Cycle I, Meeting 1, the average increased to 37.8% (Developing category), and in Meeting 2 to 45.5% (Developing category). In Cycle II, Meeting 1, the average rose to 63.4% (Almost Mastered category), and in Meeting 2 to 84.6% (Fully Mastered). It can be concluded that the night market role-playing activity can be used as an effective method to introduce financial literacy to children aged 4-5 years at TK PGRI 5 Kalipare.